Salivary and Urinary Total Antioxidant Capacity as Biomarkers of Oxidative Stress in Humans. (7th February 2016) - Peluso, Ilaria; Raguzzini, Anna
Abstract : Total Antioxidant Capacity (TAC) is a biomarker often used in order to investigate oxidative stress in many pathological conditions. Saliva and urine can be collected noninvasively and represent attractive diagnostic fluids for detecting biomarkers of various pathological conditions. The reviewed case-control and intervention studies that measured salivary or urinary TAC revealed that diseases, antioxidant foods, or supplements and age, gender, and lifestyle factors influenced salivary or urinary TAC. Salivary and urinary TAC were particularly affected by oral or renal status, respectively, as well as by infection; therefore these factors must be taken into account in both case-control and intervention studies. Furthermore, some considerations on sample collection and normalization strategies could be made. In particular, unstimulated saliva could be the better approach to measure salivary TAC, whereas 24 h or spontaneous urine collection should be chosen on the basis of the study outcome and of the creatinine clearance. Finally, the uric acid-independent TAC could be the better approach to evaluate red-ox status of body, in particular after nutritional interventions and in diseases associated with hyperuricaemia.